2022
DOI: 10.1002/jdd.12938
|View full text |Cite
|
Sign up to set email alerts
|

Dental students’ perceptions of the wildcard as a novel teaching technique in case‐based learning

Abstract: Objective: Cases used in case-based learning should be realistic, relatively difficult, engaging, and educational to maximize clinical knowledge and skills. Data are needed to support the effectiveness of existing and new techniques to ensure these case attributes. The purpose of this study was to explore dental students' perceptions of the wildcard technique in case-based learning. This novel technique aims to ensure key case attributes by adding new information to the analysis of a case that challenges the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…or are typical, real-world examples while using a CBL technique. Intense interaction between participants builds knowledge as they evaluate a case as a group using this learner-centered approach (Maia et al, 2023;Perez et al, 2022).…”
Section: Conceptual/theoretical Frameworkmentioning
confidence: 99%
“…or are typical, real-world examples while using a CBL technique. Intense interaction between participants builds knowledge as they evaluate a case as a group using this learner-centered approach (Maia et al, 2023;Perez et al, 2022).…”
Section: Conceptual/theoretical Frameworkmentioning
confidence: 99%
“…A concern is that the development of these HOTS and practical application skills in dentistry has limited reproducibility due to crowded classrooms and limited lecture hours (van der Hoeven et al, 2020; Whitney et al, 2016). Conventional instructor‐centred models that reward memorization are insufficient to develop these skills (Perez et al, 2022). Hence, this recent study suggested the FC model supported with video‐driven discussion in DE.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It is necessary for DSs to take their responsibilities for learning and to develop higher‐order thinking skills (HOTS) rather than teacher‐centred instruction (Gallardo et al, 2022). Perez et al (2022) argue that dental education (DE) requires a problem‐ or case‐based constructivist learning approach promoting active engagement of learners. Traditional teacher‐centred approaches fall short of developing high‐order mental skills such as problem‐solving, critical thinking, and analysis in students (Perez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation